Administration of Live-Attenuated Newcastle Disease (ND) Vaccines Derived from B1 and LaSota Strain and Their Effect on Broiler Antibody Titers (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2022)
Newcastle Disease is a contagious disease caused by Avian Paramyxovirus and infects different types of poultries including broiler. Vaccination as a preventive effort against the ND virus could employ both attenuated and inactivated vaccines. This study aims to identify the effect of administering live-attenuated LaSota and B1 ND vaccines against broiler antibody titers. This experiment employed 54 DOCs and was divided into 3 groups of treatments. Vaccination was performed at the age of 3 days old through eye drop administration. Blood specimens were taken from vena brachialis at the age of 7, 14, 21 days old. Hemagglutination Inhibition (HI) assay was analyzed using One-Way Analysis of Variance (ANOVA) followed by Least Significant Different (LSD) test if the probability is significant (P